A new screening instrument for disability in low-income and middle-income settings: application at the Iganga-Mayuge Demographic Surveillance System (IM-DSS), Uganda. Issue 12 (19th December 2014) - Bachani, Abdulgafoor M; Galiwango, Edward; Kadobera, Daniel; Bentley, Jacob A; Bishai, David; Wegener, Stephen; Hyder, Adnan A
Abstract : Objective: The measurement of disability in low-income countries is recognised as a major deficiency in health information systems, especially in Africa. The Iganga and Mayuge Demographic Surveillance System (IM-DSS) in Uganda provides a special opportunity to develop population-based data to inform national health policies and evaluate innovations in assessing the burden of disability in Uganda. In this study, we apply a new instrument to screen for physical disabilities at the IM-DSS. The study utilised a modified version of the short set of questions proposed by the Washington Group on Disability Statistics. The instrument was applied at the household level and information was collected on all individuals over the age of 5, who were residents of the IM-DSS. Setting: The study was based at the IM-DSS, which covers the parts of Iganga and Mayuge districts in Eastern Uganda. Participants: 57 247 individuals were included in the survey, with 51% of the study population being women. Primary outcomes: Activity limitations Results: The overall prevalence of physical disability at the IM-DSS was 9.4%, with vision being the most common type of difficulty reported in this population, and communication being least prevalent. Disability was less likely to be observed among males than their female counterparts (OR 0.75; 95% CI 0.71 to 0.81; p<0.001). Statistically significant associations were found between disability and increasing age, as well as disability and decreasing household wealth status. Conclusions: This study shows that the modified short set of questions can be readily applied in a DSS setting to obtain estimates on the prevalence and types of disability at the population level. This instrument could be adapted for use to screen for disability in other LMIC settings, providing estimates that are comparable across different global regions and populations.